The Influence of Job Rotation and Work Motivation on the Performance of Employees at the Faculty of Economics and Business, University of Lampung - Sri Sunarsih; Dian Kagungan; Devi Yulianti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the influence of job rotation and work motivation on employee performance at the Faculty of Economics and Business, University of Lampung. The background of this research is based on the importance of employee performance in supporting the achievement of organizational goals, as well as the phenomenon of fluctuations in performance and employee discipline levels, where job rotation and work motivation are considered factors that have the potential to significantly influence employee performance. This study uses a quantitative approach with an associative method, and the population consists of all 70 employees of the Faculty of Economics and Business, University of Lampung. The data analysis technique employs multiple linear regression using SPSS software, including classical assumption tests, t-test (partial), F-test (simultaneous), and coefficient of determination test (RÂ²). The results show that partially, job rotation does not have a significant effect on employee performance (sig. 0.182 0.05), although it has a positive relationship direction, while work motivation has a positive and significant effect on employee performance (sig. 0.000 0.05) with a regression coefficient of 0.573, making it the dominant variable in this study. Simultaneously, job rotation and work motivation have a significant effect on employee performance with an F-value of 55.022 and a significance level of 0.000. The coefficient of determination (RÂ²) value of 0.625 indicates that 62.5% of the variation in employee performance can be explained by these two variables, while the remaining is influenced by other factors outside this study. This research confirms that work motivation has a more dominant role than job rotation in improving employee performance.